Alternate bar dynamics in response to increases and decreases of sediment supply - Bankert, Andrew, author; Nelson, Peter, advisor; Bledsoe, Brian, committee member; Wohl, Ellen, committee member (Colorado State University. Libraries, 2016)
Gravel-bed rivers can accommodate changes in sediment supply by adjusting their bed topography and grain size in both the downstream and cross-stream directions. Under high-supply aggradational conditions, this can result in spatially non-uniform stratigraphic patterns, and the morphodynamic influence of heterogeneous stratigraphy during subsequent degradational periods is poorly understood. We conducted an experiment in an 18.3 m long, 1.2 m wide straight rectangular channel where we developed alternate bars in a gravel-sand mixture under constant discharge and sediment supply then developed stratigraphy over existing bars through aggradation with two supply increases. The supply was then reduced back to the initial supply rate, causing degradation through that self-formed stratigraphy. We collected stratigraphic samples and made frequent measurements of the bed topography and flow depth, which were used with a two-dimensional hydrodynamic model to characterize flow conditions throughout the experiment. Migrating alternate bars stabilized during the first equilibrium phase creating bed surface sorting patterns of coarse bar tops and fine pools. During the first supply increase the bars remained stable as the pools aggraded. During the second supply increase the pools aggraded further, causing the boundary shear stress over the bar tops to increase until the bars gained the capacity to migrate and eventually stabilize in new locations. As aggradation occurred, the original sediment sorting patterns were preserved in the subsurface. During the degradational phase, the pools experienced incision and the bars eroded laterally, but this lateral erosion ceased when coarse sediment previously deposited during the bar-building phase became exposed. Our results suggest that if a sediment supply increase is capable of filling the pools it can cause stable bars to migrate and the bed to be reworked. Our findings also show that heterogeneous stratigraphy can play an important role in determining whether bars persist or disappear after a sediment supply reduction.
Keywords: flume; sediment supply; alternate bar; stratigraphy; fluvial geomorphology